MR Imaging of the Brain in Patients Cured of Acute Lymphoblastic Leukemia—the Value of Gradient Echo Imaging - Chan, M.S.M.; Roebuck, D.J.; Yuen, M.-P.; Li, C.-K.; Chan, Y.-L. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Hemosiderin and white matter lesions are 2 of the most common neurologic complications found on MR imaging that may be related to cranial irradiation and intrathecal methotrexate (MTX) therapy in childhood acute lymphoblastic leukemia (ALL). We evaluated the brains of patients previously treated for ALL with cranial irradiation and intrathecal MTX with MR imaging and tested the hypothesis that these patients have more MR evidence of central nervous system (CNS) injury than control patients who are in complete remission following systemic chemotherapy without cranial irradiation.METHODS AND MATERIALS: ALL patients recruited from a pediatric cancer center data base were examined at 1.5T by using Tl-weighted, T2-weighted, gradient echo (GE), and fluid-attenuated inversion recovery sequences. Patients treated in childhood for solid extracranial neoplasms were used as controls.RESULTS: Lesions consistent with old hemorrhage were detected in 23 (55%) of the ALL patients and in none of the control patients (P <.001). Of the 62 hemorrhages detected on the GE images, only 9 (15%) were shown on T2-weighted images. White matter abnormalities were found in 2 ALL patients (5%) and one control patient (5%). Old infarcts were seen in 2 ALL patients (10%).CONCLUSION: Cerebral hemorrhages related to radiation-induced vascular malformations, most of which are asymptomatic, are much more common in survivors of childhood ALL than previously thought. GE sequencing is more sensitive in detecting hemorrhagic lesions than T2-weighted sequencing and is to be included in imaging protocols for follow-up study of patients after cerebral radiation therapy.